Preventing Obesity in Patients through Community Health Prevention Programs - Umair Jamal; Cora Hoover; Candice Wong; Amin Azzam (Association of American Medical Colleges, 2014)
Abstract Like many underserved and low socio-economic urban neighborhoods, the city of Richmond, CA faces several health-related problems, including childhood obesity, pollution and low air quality, gang violence, high unemployment, and lack of access to needed healthcare services, including substance abuse and mental health resources. This "public health oriented" Problem Based Learning (PBL) case uses the framework of a new primary care clinician evaluating a child with asthma and obesity to consider "upstream" interventions that physicians might use to indirectly improve the health of the neighborhood by working with community health organizations to prevent and/or minimize health disparities. Having a Public Health understanding such as the associated behavioral and social risk factors for obesity can help in improving the health of patients. The geographic specifics of this case are easily modifiable to represent local urban or rural underserved neighborhoods. This PBL case has been used in a predominately PBL-based pre-clerkship medical school curriculum for several years. This work conveys that providing primary care through a "Public Health lens" is a significant benefit to treating patients with certain diseases, especially chronic diseases such as obesity and asthma. The purpose of this work is to make medical students aware of the multiple "upstream" ways they could improve the health of patients.